2013
DOI: 10.1176/appi.ajp.2012.12070991
|View full text |Cite
|
Sign up to set email alerts
|

Nonpharmacological Interventions for ADHD: Systematic Review and Meta-Analyses of Randomized Controlled Trials of Dietary and Psychological Treatments

Abstract: Free fatty acid supplementation produced small but significant reductions in ADHD symptoms even with probably blinded assessments, although the clinical significance of these effects remains to be determined. Artificial food color exclusion produced larger effects but often in individuals selected for food sensitivities. Better evidence for efficacy from blinded assessments is required for behavioral interventions, neurofeedback, cognitive training, and restricted elimination diets before they can be supported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

48
957
7
40

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 986 publications
(1,052 citation statements)
references
References 83 publications
48
957
7
40
Order By: Relevance
“…A number of reviews and meta-analyses have addressed the literature regarding EEG-nf treatment for ADHD (Arns et al, 2014;Arns, Ridder, & Strehl, 2009;Lofthouse et al, 2012;Sonuga-Barke et al, 2013), epilepsy (Tan et al, 2009), depression and anxiety (Hammond, 2005), Parkinson's disease (Esmail & Linden, 2014), and a slew of other disorders (Hammond, 2011). Some of these accounts highlight the dearth of convincing evidence (Esmail & Linden, 2014;Lofthouse et al, 2012;Sonuga-Barke et al, 2013) while others rely on single-blinding, subpar control groups, non-peer-reviewed publications, and case studies to support EEG-nf (see Thibault et al, 2015 for a more in-depth exposition).…”
Section: Introductionmentioning
confidence: 99%
“…A number of reviews and meta-analyses have addressed the literature regarding EEG-nf treatment for ADHD (Arns et al, 2014;Arns, Ridder, & Strehl, 2009;Lofthouse et al, 2012;Sonuga-Barke et al, 2013), epilepsy (Tan et al, 2009), depression and anxiety (Hammond, 2005), Parkinson's disease (Esmail & Linden, 2014), and a slew of other disorders (Hammond, 2011). Some of these accounts highlight the dearth of convincing evidence (Esmail & Linden, 2014;Lofthouse et al, 2012;Sonuga-Barke et al, 2013) while others rely on single-blinding, subpar control groups, non-peer-reviewed publications, and case studies to support EEG-nf (see Thibault et al, 2015 for a more in-depth exposition).…”
Section: Introductionmentioning
confidence: 99%
“…Although superior to behavioral treatments in the short‐term, longer‐term efficacy has not been demonstrated [Cunill et al, 2016; Molina et al, 2009], which may be related to evidence from positron emission tomography studies for dopaminergic brain adaptation to psychostimulant medication [Fusar‐Poli et al, 2012; Wang et al, 2013]. Moreover, because of their potential for abuse and diversion, adverse effects, and unknown longer‐term brain effects, non‐pharmacological treatments are preferred, but have limited efficacy [Sonuga‐Barke et al, 2013]. …”
Section: Introductionmentioning
confidence: 99%
“…Given that ADHD is typified by poor self‐control [Schachar et al, 1993], and enhancing brain‐self‐control is the target of NF, ADHD is the psychiatric disorder where NF has been most applied, using electrophysiological neurofeedback (EEG‐NF) targeting abnormal EEG biomarkers. Meta‐analyses of randomized controlled trials (RCT) of EEG‐NF show medium effect sizes for symptom improvements [Arns et al, 2009], reduced to trends when only “probably” blinded raters are included [Holtmann et al, 2014; Sonuga‐Barke et al, 2013]. Crucially, unlike psychostimulant treatment, NF effects seem stable and longer‐lasting (up to 2 years), with no side effects [Arns and Kenemans, 2014; Gani et al, 2008; Gevensleben et al, 2010; Leins et al, 2007; Mayer et al, 2016; Steiner et al, 2014; Strehl et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…Extant research has demonstrated support for the efficacy of cognitive training programs in improving individual cognitive skills (Holmes, Gathercole, & Dunning, 2009; Klingberg et al, 2005; Melby‐Lervag & Hulme, 2013; Sonuga‐Barke et al, 2013; Wegrzyn, Hearrington, Martin, & Randolph, 2012). However, because each training program described in the literature targets different cognitive skills, the results are as diverse and varied as the programs themselves.…”
mentioning
confidence: 99%